J02 Evaluation of pilocarpine iontophoresis vs. exercise-induced sweat sodium concentrations at different exercise intensities - Harris, Christopher; Blow, Andrew; Hew-Butler, Tamara (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Differences between passive versus active sweat sodium concentration ([Na+]) may alter sodium replacement strategies. The primary purpose of this pilot trial was to compare pharmacologically induced sweat [Na+] (passive) with exercise-induced sweat [Na+] (active) at three different exercise intensities. Methods: This was an internal validation trial, reviewed by Wayne State University’s IRB (IRB 23-02-5555). WSU’s IRB determined that this retrospective, observational, data collection did not fall within the scope of human research regulations. As such, fifteen endurance cyclists participated in four cycling trials (different days, separated by a week) at three exercise intensities (50, 75, and 100% of functional threshold power/FTP) for 20 minutes. Sweat was collected prior to each trial via pilocarpine iontophoresis (passively induced sweat). Then, a macroduct™ (Wescor Inc, Logan, UT) sweat collector was affixed to the same forearm (at a different location than the passively induced sweat collection) and the athlete cycled at the given intensity to collect exercise-induced sweat. Sweat samples were analysed for sweat [Na+] immediately (Sweat Chek Conductivity Analyzer, Wescor Inc, Logan UT), which was the main outcome variable. One-way ANOVA was utilised to detect differences in passive and active sweat [Na+] levels across different exercise intensities. Statistical significance was set a priori at P < 0.05. Results: Fifteen highly trained cyclists between 19-45 years (10 male, 5 female, weight 69 ± 9 kg, FTP 4.16 ± 0.56 W/kg, passive sweat [Na+] 55.6 ± 18.5 mmol/L [range 30-89 mmol/L]) completed this trial. No statistically significant differences were noted between pre (passive) to post (active) sweat [Na+] levels during the 50% FTP, 75% FTP, or 100% FTP conditions. However, when assessing exercise-induced sweat [Na+] minus passive-induced sweat [Na+], significant differences were noted between the 50% (−12.4 ± 7.6mmol/L), 75% (1.3 ± 6.2mmol/L) and 100% FTP (7.5 ± 6.8 mmol/L) exercise intensity conditions (P < 0.001; R2 = 0.61). Although sweat rate was different between the 50% (0.62 ± 0.21 L/h), 75% (1.26 ± 0.34 L/h), and 100% FTP (1.89 ± 0.50 L/h) conditions; P < 0.001; R2 = 0.68, there were no significant associations between sweat rate versus sweat [Na+] change except for the 100% FTP condition (R2 = 0.29; P = 0.04). Conclusions: Exercise-induced sweat approximates pharmacologically induced sweat at cycling intensities around 75% FTP, with lower sweat [Na+] readings at lower (50% FTP) intensities and higher sweat [Na+] readings at higher (100% FTP) cycling intensities.